Brinzolamide-Loaded Nanoemulsions: In vitro Release Evaluation - Mohammad Mehdi Mahboobian; Seyed Mohsen Foroutan; Reza Aboofazeli (Iranian Journal of Pharmaceutical Sciences, 2016)
The aim of this investigation was to design and develop nanoemulsions (NEs) as novel ophthalmic delivery systems for brinzolamide (BZD). Phase behavior of quaternary systems composed of triacetin and CapryolTM 90 (selected oils, screened through the solubility studies), various surfactants (namely, Cremophor RH 40, Brij 35, Labrasol and tyloxapol), Transcutol P (as co-surfactant) and water at different surfactant/co-surfactant weight ratios (Rsm) was investigated by the construction of phase diagrams. Formulations were taken from the o/w NE region on the phase diagrams, depending on the extent of NE domain. The spontaneous emulsification method was used to prepare various formulations containing 0.4 wt% of the drug. The nanosized character of NEs was evaluated, the cumulative drug release from of the selected formulations was determined for a period of 6 h, using a dialysis sac technique and the release efficiency for NEs was calculated. The therapeutic efficacy of the selected BZD-loaded NEs to lower the IOP was assessed by the calculation of various pharmacodynamic parameters (ie., Emax, Tmax AUC0-6h). In all cases, the average size of the droplets was found to be less than 40 nm. In vitro release studies indicated that the release efficiency in most of the NEs was higher as compared to the BZD ophthalmic suspension. Comparison of the pharmacodynamics parameters confirmed the equivalent efficacy of most BZD formulations.